2021
DOI: 10.56301/awal.v4i1.121
|View full text |Cite
|
Sign up to set email alerts
|

Model Pengembangan Desa Wisata Berbasis Kearifan Lokal Sebagai Strategi Peningkatan Ekonomi Masyarakat Di Desa Cupang Kecamatan Gempol Kabupaten Cirebon

Abstract: Desa Cupang Kecamatan Gempol Kabupaten Cirebon menyimpan keindahan alam yang dapat dikembangkan menjadi kawasan pariwisata. Kawasan Batu Lawang dan Petilasan Sunan Bonang yang terletak di desa Cupang menjadi daya tarik tersendiri dengan karakteristik yang khas, unik dan menarik untuk dikembangkan menjadi objek wisata. Pengembangan objek wisata dengan memperhatikan kearifan lokal dapat menjadi salah satu strategi dalam meningkatkan taraf perekonomian masyarakat desa. Namun sayangnya saat ini potensi yang ada di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
3
0
3
Order By: Relevance
“…Based on the results of research conducted, the acceleration of tourism village development in Samosir Regency still faces many obstacles, both in terms of facilities and infrastructure and social aspects related to community behavior, especially in the Pusuk Buhit area. The development of tourist villages oriented towards local wisdom is the main target of regional development in Samosir Regency, this is in accordance with the opinion of Jubaedah [23], Syafrizal [24] and Tanjung [25], who argue that local wisdom is customs and habits that have become traditions in certain Traditions within certain social groups, passed down through successive generations, endure as a community culture of significant value, deeply ingrained to contribute to the enhancement of the local economy. However, Chiu underscores the influence of public perspectives on natural conditions, revealing low trust, which adversely affects the government's capacity to establish enduring opportunities aligned with long-term tourism development.…”
Section: Resultssupporting
confidence: 68%
“…Based on the results of research conducted, the acceleration of tourism village development in Samosir Regency still faces many obstacles, both in terms of facilities and infrastructure and social aspects related to community behavior, especially in the Pusuk Buhit area. The development of tourist villages oriented towards local wisdom is the main target of regional development in Samosir Regency, this is in accordance with the opinion of Jubaedah [23], Syafrizal [24] and Tanjung [25], who argue that local wisdom is customs and habits that have become traditions in certain Traditions within certain social groups, passed down through successive generations, endure as a community culture of significant value, deeply ingrained to contribute to the enhancement of the local economy. However, Chiu underscores the influence of public perspectives on natural conditions, revealing low trust, which adversely affects the government's capacity to establish enduring opportunities aligned with long-term tourism development.…”
Section: Resultssupporting
confidence: 68%
“…Determination of Goals and Objectives:The initial step is to identify the main goal of this assistance, such as increasing public awareness about the potential of ecotourism, increasing the number of tourists, or increasing local economic income. (Jubaedah & Fajarianto, 2021) (Nanang et al, 2023). Specific targets must also be set, such as a percentage increase in tourist visits, or an increase in the number of social media followers.…”
Section: Implementation Methodsmentioning
confidence: 99%
“…The agro-tourism potentials of the object of study are identified and analyzed with indicators such as structure and infrastructure, accessibility, village attractiveness, participation and empowerment of village people, demeanor and cordiality of village people, agriculture type, tenacity against disaster, other tourism objects, and values that constitute local wisdom [21][22][23].…”
Section: Methods Of Researchmentioning
confidence: 99%